A twenty-first-century Olympic and Amateur Sports Act - Koller, D. L. (Vanderbilt Journal of Entertainment & Technology Law, 2018)
Recent scandals involving national governing bodies for sport and allegations of athlete abuse have captured media attention. The most recent, focusing on the actions of USA Gymnastics, prompted Congress to propose legislation to require better protections for Olympic Movement athletes. Signed into law on February 14, 2018, the Protecting Young Victims from Sexual Abuse and Safe Sport Authorization Act of 2017 designates the United States Center for SafeSport (SafeSport) as the independent organization charged with exercising jurisdiction over the United States Olympic Committee (USOC) and sport national governing bodies to safeguard amateur athletes against all forms of abuse. Congress`s instincts in this regard are admirable, and the empowerment of SafeSport is critically important. However, this Article asserts that the issue targeted by the recently enacted legislation must be viewed in the context of the overall regulation of Olympic and amateur sport in the United States. In doing so, Congress should consider more comprehensive reform that goes beyond the issue of athlete abuse. Instead, Congress should further amend the Ted Stevens Olympic and Amateur Sports Act, the statute establishing the USOC and regulating the US Olympic program, to address the new realities of Olympic and amateur sport in the United States. Specifically, this Article asserts that the statute should be amended to require reforms in three areas: athlete health and well-being, whistleblowing, and gender equity in the US Olympic program. In addition, this Article argues that Congress should enact a true amateur sports act, with a primary feature being the creation of an entity charged with developing an agenda and reforms for youth and amateur (non-Olympic) sports.